2017
DOI: 10.1039/c7nr02420g
|View full text |Cite
|
Sign up to set email alerts
|

Nanocylindrical confinement imparts highest structural order in molecular self-assembly of organophosphonates on aluminum oxide

Abstract: We report the impact of geometrical constraint on intramolecular interactions in self-assembled monolayers (SAMs) of alkylphosphonates grown on anodically oxidized aluminum (AAO). Molecular order in these films was determined by sum frequency generation (SFG) spectroscopy, a more sensitive measure of order than infrared absorption spectroscopy. Using SFG we show that films grown on AAO are, within detection limits, nearly perfectly ordered in an all-trans alkyl chain configuration. In marked contrast, films fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Since this is obviously not the case and the strong 𝑑 + band was observed independent of the surface pressure used during Langmuir-Blodgett transfer of the layer (Supporting Information) we take the strength of the 𝑑 + band relative to the 𝑟 + band as an qualitative indicator for the presence of gauche conformations in the dodecyl chain from the phosphonic acid anchor to the triazole group of our monolayer (see Figure 1). This is consistent with earlier works, [60][61][62] where self-assembled monolayers of alkyl phosphonic acids with different chain lengths (C8 to C18) were studied on aluminum oxide as well as on other interfaces. The lateral attractive van der Waals interactions in monolayers are only in the presence of very long alkyl chains e.g.…”
Section: Photo-switchable Aap Monolayers In Equilibriumsupporting
confidence: 92%
“…Since this is obviously not the case and the strong 𝑑 + band was observed independent of the surface pressure used during Langmuir-Blodgett transfer of the layer (Supporting Information) we take the strength of the 𝑑 + band relative to the 𝑟 + band as an qualitative indicator for the presence of gauche conformations in the dodecyl chain from the phosphonic acid anchor to the triazole group of our monolayer (see Figure 1). This is consistent with earlier works, [60][61][62] where self-assembled monolayers of alkyl phosphonic acids with different chain lengths (C8 to C18) were studied on aluminum oxide as well as on other interfaces. The lateral attractive van der Waals interactions in monolayers are only in the presence of very long alkyl chains e.g.…”
Section: Photo-switchable Aap Monolayers In Equilibriumsupporting
confidence: 92%
“…Since this is obviously not the case and the strong 𝑑 + band was observed independent of the surface pressure used during Langmuir-Blodgett transfer of the layer (Supporting Information) we take the strength of the 𝑑 + band relative to the 𝑟 + band as a qualitative indicator for the presence of gauche conformations in the undecyl chain from the phosphonic acid anchor to the triazole group of our monolayer (see Figure 1). This is consistent with earlier works, [60][61][62] where self-assembled monolayers of alkyl phosphonic acids with different chain lengths (C8 to C18) were studied on aluminum oxide as well as on other interfaces. The lateral attractive van der Waals interactions in monolayers are only in the presence of very long alkyl chains e.g.…”
Section: Photo-switchable Aap Monolayers In Equilibriumsupporting
confidence: 92%
“…In fact, for the air-water interfaces from the pure surfactant solutions, a small CH2/CH3 SFG intensity ratio (< 0.1) of the symmetric stretching bands is indicative for well-ordered alkyl chains at the interface that show a low density of gauche conformations and predominant all-trans conformation. In addition, previous studies [58][59][60] have shown that alkyl chain ordering is not only a function of surface coverage 59,58 but also a function of the surfactants alkyl chain length. 60 That is because shorter chains lead to a decrease in lateral dispersive interactions and result in lower molecular order and higher density of gauche conformations.…”
Section: Correlation Between Bulk and Interfacial Propertiesmentioning
confidence: 92%
“…In addition, previous studies [58][59][60] have shown that alkyl chain ordering is not only a function of surface coverage 59,58 but also a function of the surfactants alkyl chain length. 60 That is because shorter chains lead to a decrease in lateral dispersive interactions and result in lower molecular order and higher density of gauche conformations. In our spectra, however, the highest molecular order was observed for C12TAB surfactants.…”
Section: Correlation Between Bulk and Interfacial Propertiesmentioning
confidence: 92%